Prevalence of dental fluorosis and its relationship with water fluoride levels among school students in southern lran - Davari A.R (Payesh, 2007)
Objective (s): We investigated the prevalence of dental fluorosis and its relationship with fluoride levels in drinking water among children aged 12-15 years old in southern Iran. Methods: The study was cross-sectional with cluster random sampling. We studied 406 students (186 female and 220 male) in Bastak and its suburbs, which are administratively subordinate to the city or Bandar Lengeh in the southern province or Honnozgan. Results: High level water fluoride account for the high prevalence and severity or dental Iluorosis in the region. Fluoride levels of 1.55 PPM in the village of Harang versus levels of 0.75 PPM in Jonahs correspond to the greater prevalence of dental fluorosis in the fonner locality. We did not detect a statistically significant relationship between age and fluorosis. Conclusion: Considering the average water fluoride or I.OS PPM, average temperature of26.1°C, and the community fluorosis index (CFI) of 0.83 for this area, we conclude that levels of fluoride in the regionchr('39')s drinking water are well above the W.H.O. recommendations.